Alkaline fermentation of waste activated sludge with calcium hydroxide to improve short-chain fatty acids production and extraction efficiency via layered double hydroxides. (May 2019) - Ma, Xiao; Ye, Jiongjiong; Jiang, Li; Sheng, Liang; Liu, Jianyong; Li, Yu-You; Xu, Zhi Ping
Graphical abstract: Highlights: Adding Ca(OH)2 was proposed to improve SCFAs extraction rate via LDHs synthesis. Carbonate and phosphate could be removed effectively by adding Ca(OH)2 . SCFAs levels intercalated into SCFAs-LDHsCa was significantly improved. Abstract: Ca(OH)2 addition was proposed to improve short chain fatty acids (SCFAs) production via alkaline fermentation of waste activated sludge (WAS), with CO3 2− and PO4 3− being removed simultaneously, so that the SCFAs extraction efficiency could be improved. Alkaline fermentation of WAS with Ca(OH)2 and NaOH addition were performed respectively, and the efficiencies of SCFAs extraction from the fermentation liquids via in situ layered double hydroxides (LDHs) were investigated. The results showed that, the SCFAs production was much more improved with NaOH addition than that with Ca(OH)2 addition. However, the SCFAs contents in the synthesized SCFAs-LDH were 6.7 ± 0.4 mg COD/L (control), 12.4 ± 0.5 mg COD/L (with NaOH addition) and 17.4 ± 0.4 mg COD/L (with Ca(OH)2 addition), respectively. This means that Ca(OH)2 addition is an effective way to improve SCFAs extraction from fermentation liquid of WAS.